Aroma profile of the anise‐like odour mushroom Cortinarius odorifer. (26th May 2015) - Kleofas, Vanessa; Popa, Flavius; Fraatz, Marco A.; Rühl, Martin; Kost, Gerhard; Zorn, Holger
Abstract The aroma compounds of fruiting bodies of C. odorifer were extracted by means of liquid/liquid extraction and purified by solvent assisted flavour evaporation (SAFE). The odour active compounds were identified by gas chromatography‐mass spectrometry and olfactometry on two columns of different polarity and described by sensory detection. The volatilom of C. odorifer is reported here for the first time. Additionally, an aroma extract dilution analysis (AEDA) was performed to identify the main flavour compounds. Finally, the volatiles were quantified by GC flame ionization detection (GC‐FID). The main odour compound of C. odorifer was methyl p‐anisate with an FD factor of 8, 192 and a concentration of 120 mg kg‐1. Methyl p‐anisate was also the compound responsible for the characteristic anise‐like odour of C. odorifer. Copyright © 2015 John Wiley & Sons, Ltd.